Relationship between Transaminase Enzyme Levels and Severity of Dengue Fever - Sidabutar, Wita Lestari; Saragih, Restuti Hidayani; Rohmawati, Lili; Sinaga, Bintang Yinke Magdalena (Universitas Muhammadiyah Yogyakarta, 2025)
Since dengue hemorrhagic fever (DHF) can cause liver damage, aminotransferase levels as liver function test may be useful in predicting the severity of dengue hemorrhagic fever. The purpose of this study was to determine the relationship between transaminase enzyme levels and the severity of dengue hemorrhagic fever. This study used analytic observational approach with cross-sectional design. The data used was secondary data, namely medical records of H. Adam Malik Hospital and Hospital of Prof. Dr. Chairuddin P. Lubis University of North Sumatera. From a total of 65 patients included, there were 63.1% (41 patients) with DHF grade 1, 29.2% (19 patients) were DHF grade 2, 6.2% (4 patients) were DHF grade 3 and 1.5% (1 medical record) were DHF grade 4. For aminotransferase level 56.9% (37 records) had elevated SGPT levels and 92.3% (60 records) had elevated SGOT levels, it was found that there was no relationship between increased levels of SGPT and SGOT with the severity of DHF (SGPT p = 0.628 and SGOT p = 1.00). There is no association between the elevations of transaminase enzyme levels and the severity of DHF.